La pêche à la morue des Français d’Amérique du Nord de 1500 à 1763: un atout dans la géopolitique française - Mimeault, Mario (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2018)
The sedentary fishery of the French residing in North America became an element of support for France’s imperial metropolitan policy as it established claims on disputed fishing areas. As a result, France engaged in a strategy of appropriation of the New World – a policy affirmed diplomatically by François I and defended by his successors. This article establishes how the colonial sedentary fishery helped lead to the appropriation of the New World by France until this fishery was abandoned at the end of the French Regime.